Exploring Learner Perceptions of AI-Driven Chatbots in a Zimbabwean Higher Education Context - Fungai Mushonga; Andrew Mangena (Scientia Publica Media, 2026)
Artificial intelligence (AI) has found its way into higher education institutions through rapid advancements in technology. Zimbabwe’s Ministry of Higher and Tertiary Education, Science, Innovation and Technology Development (MHTESITD) adopted Heritage-based Education 5.0 for the digitalisation of operations and curricula in Higher Education (HE). This has put pressure on institutions to adapt and seek ways of accelerating the AI-driven digitalisation of curricula and activities. Currently, there are ongoing dialogues and debates on the ethical and societal implications of adding AI into the curriculum. The purpose of the study was to investigate the perceptions of learners and intentions to adopt and use AI-chatbots in a higher education institution (HEI). The learner’s preferences were explored using a qualitative research approach within an interpretivist paradigm. Semi-structured interviews were conducted in the pilot study to test the validity of the questions, and an online open-ended questionnaire was used to collect primary data that was thematically analysed. Ethical considerations such as privacy, consent, credibility, and trustworthiness were ensured in the study. Analysis of results revealed that participants would comfortably increase their use of AI-chatbots on condition that the HE institutions align plagiarism regulations with ethics, ensure data privacy, accuracy, and security in learning and teaching. The relevance of this study shows how learners have adopted AI technologies while leaving the HE institutions behind in the digitalisation of operations and curricula. These findings can be used in active participation in policy debates and considerations for inclusive, effective, and ethical adoption of AI-chatbots in HE.